Removal of Riprap within Channelized Rivers: A Solution for the Restoration of Lateral Channel Dynamics and Bedload Replenishment? - Anaïs Arfeuillère; Johannes Steiger; Emmanuèle Gautier; Stéphane Petit; Erwan Roussel; Franck Vautier; Olivier Voldoire; Julien Saillard (Applied Sciences, 2023)
Riverbank erosion is an essential morphodynamic process for the improvement of river health and the ecohydrogeomorphological functioning of alluvial rivers. Lateral channel dynamics and sediment supply caused by bank erosion largely create and maintain heterogeneous in-channel habitats for fauna and aquatic or riparian plant species. However, humans very early started to stabilize riverbanks in order to favour navigation or to prevent valuable land and infrastructures close to the channel from eroding. During the 20th century, bank protection works such as riprap considerably increased and blocked lateral channel erosion, causing a loss of local sediment supply, which in turn resulted in a decrease in local bedload transport and channel incision. The aim of the article is to evaluate to what extent riprap removal may be an efficient restoration measure in terms of the reactivation of bank erosion and the replenishment of the local bedload in gravel-bed floodplain rivers with a sufficient amount of freedom space. An experimental in situ restoration approach was chosen. First, riprap was removed at two geomorphologically contrasting sites on the Allier River, France. Second, bank retreat was monitored, and the volumes eroded were quantified using photogrammetric and LiDAR surveys. Third, in the case of post-restoration bank erosion, grain size and morphological channel evolution analyses were carried out. Our results suggested that the removal of riprap is an effective measure for certain but not all channelized floodplain reaches. The geomorphological and sedimentary contexts are two criteria that should be considered when selecting sites for restoration. Thus, this study helps river managers to better target the criteria to be taken into account for the selection of sites with high potential for the restoration of lateral channel dynamics.